2014
DOI: 10.1136/bjophthalmol-2014-305371
|View full text |Cite
|
Sign up to set email alerts
|

Uveal melanoma hepatic metastases mutation spectrum analysis using targeted next-generation sequencing of 400 cancer genes

Abstract: Further studies are required to confirm FBXW7 implication in UM tumorigenesis. Elucidating the molecular mechanisms underlying UM tumorigenesis holds the promise for novel and effective targeted UM therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 22 publications
(27 reference statements)
2
22
0
Order By: Relevance
“…39,40 Likewise, BAP1 and SF3B1 mutations are mutually exclusive, as are EIF1AX and SF3B1 mutations, whereas TERT mutations appear to coexist specifically with GNA11 or EIF1AX mutations. 38,[41][42][43][44]…”
Section: Genetic Mutations In Uveal Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Likewise, BAP1 and SF3B1 mutations are mutually exclusive, as are EIF1AX and SF3B1 mutations, whereas TERT mutations appear to coexist specifically with GNA11 or EIF1AX mutations. 38,[41][42][43][44]…”
Section: Genetic Mutations In Uveal Melanomamentioning
confidence: 99%
“…41 SF3B1 is reported in approximately 15% of primary uveal melanomas but has also been observed in the hepatic metastases of uveal melanoma. 43…”
Section: Sf3b1mentioning
confidence: 99%
“…Loss of BAP1 protein expression was frequent, and mutations in SF3B1 were rare. Most recently, Luscan et al examined five hepatic MUMs using a targeted next-generation sequencing (NGS) approach of 409 cancer genes, confirming recurrent mutations in GNAQ, GNA11, BAP1, and SF3B1, and identifying a mutation in the tumor suppressor gene FBXW7 in one of the hepatic MUMs (Luscan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence from this investigation shows despite the overall appearance of global integrity found in earlier studies, there is much flexibility in the size of amplifications of 8q gain as well as the focal nature of changes affecting 8p. Uveal melanoma have recently been suggested as having a low level of mutational events in targeted cancers genes 33 and through larger scale sequencing shown to be relatively genetically stable. 34 Recent studies of cutaneous melanomas demonstrated that they can have a crisis of focal instability related to a particularly poor outcome, termed chromothripsis.…”
Section: Discussionmentioning
confidence: 99%